PENINGKATAN KUALITAS PUBLIKASI ILMIAH DAN PENELITIAN BAGI GURU SLTA DENGAN PEMANFAATAN SOFTWARE REFERENSI - Afdhil Hafid; Harun Mukhtar; Regiolina Hayami; Yulia Fatma; Mitra Unik; Hasanuddin Hasanuddin; Yoze Rizki (Jurnal Pengabdian UntukMu NegeRI, 2018)
Republic of Indonesia Law No. 14 of 2005 describes teachers as professional educators with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students in the formal education listed. The teacher has an important role in planning and implementing the learning process, so as to obtain opportunities to improve competence. One of the activities that must be carried out by teachers in developing their competence as teachers is scientific publications, which are listed in Article 11 of the Minister of PAN & RB Regulation No.16 of 2009 concerning teacher functional positions. In designing scientific publications there are stages and methods that are different from other papers. The research work comes from the research activities carried out so that it can be a reference in the follow-up of educational activities. The existence of information technology devices makes it easy for teachers to carry out research activities to publish them. The more research carried out at this time is not necessarily comparable with the quality of research. The demand to fulfill good and correct reference criteria is a challenge for teachers in the stages of reviewing and following up on publications. This service activity provides other insights into better article writing and reference techniques using computer-assisted devices. Problems with the obstacles faced so far by the teacher in writing are expected to be solved so that joint efforts in creating an environment of professionalism in education can be realized.